2016
DOI: 10.4314/ejesm.v8i2.5s
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity Effect of Spent Oil on Jatropha curcas Seedlings used in Soil Phytoremediation

Abstract: Soil contamination by Spent Lubricating Oil (SLO) is a growing concern in many African

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…This could be as a result of reduce in photosynthesis of plant leaves due to coating of roots with spent oil which could have disrupted the architecture, and led to decrease in nutrients uptake by the plants (Khan et al 2013;Pezeshki et al, 2000) and other physiological and biochemical activities. This finding conforms to the earlier study of Idowu and Fayinminnu (2015) on Jatropha curca with significant reduction of growth parameters from SLO polluted soil.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This could be as a result of reduce in photosynthesis of plant leaves due to coating of roots with spent oil which could have disrupted the architecture, and led to decrease in nutrients uptake by the plants (Khan et al 2013;Pezeshki et al, 2000) and other physiological and biochemical activities. This finding conforms to the earlier study of Idowu and Fayinminnu (2015) on Jatropha curca with significant reduction of growth parameters from SLO polluted soil.…”
Section: Discussionsupporting
confidence: 93%
“…The study site and all the methods carried out in this study followed the same procedures as earlier reported according to Idowu and Fayinminnu (2015; Top soil samples (0-15 cm) were collected randomly with a Dutch auger and trowel from the Forest Floor of Acacia Plantation of the Forestry Research Station. The soil was thoroughly mixed and passed through a 2mm sieve to remove the non-soil particulate.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…curcas has been known to be a good phytoremediating plant capable of surviving in adverse heavy metal contamination, for instance, Idowu and Fayinminnu [5] investigated the phytotoxicity of spent oil contaminated soil on J. curcas, while several studies have also demonstrated its ability to withstand metal toxicities. Liang et al, [6] showed that J. curcas exhibited inherent tolerance to cadmium and lead stress and thus a good candidate for phytoremediation; the growth response of J. curcas to heavy metal contaminated sludge has been reported by several authors [7], [8], [9], [10] with various phytotoxic effects observed dependent on the level of heavy metals present in the growth media.…”
Section: Comparative Growth Response Of Three Jatropha Species On Heamentioning
confidence: 99%
“…The research therefore aims at evaluating the comparative phytotoxcity effect of heavy metal contamination on J. curcas, J. gossypifolia and J. multifida with a view to find a common behavioural pattern in the Jatropha spps and consequently, an alternative Jatropha specie with phytoremediating potential. (5) days, sieved using 2mm mesh size and analysed for heavy metals specifically, lead, chromium, Nickel, Zinc and cadmium. This is to ascertain the level of contamination by the metals and thus the effect on the growth factors of the plants.…”
Section: Comparative Growth Response Of Three Jatropha Species On Heamentioning
confidence: 99%